Aplikasi Pencarian Dan Pemesanan Hotel di Kota Pagar Alam Berbasis Web - Febriansyah Febriansyah; Siti Muntari (Fakultas Teknik Universitas Hamzanwadi, 2021)
This study aims to produce Search and Booking Hotel Application in the city of Pagar Alam web-based which can facilitate Hotel Owners in managing data and also facilitate parties who want to get information quickly, and can be accessed anytime and anywhere. At Hotel in Kota Pagar Alam information about Hotel is currently still manual, namely visitors must come directly to Kota Pagar Alam Hotel to find information and see the condition of Hotel in Kota Pagar Alam so visitors need a long time to find information about Hotel , the purpose of making the application easier for users to search and book Hotel in the City of Pagar Alam so that users can more easily find information about the Hotel Pagar Alam. Data collection methods in this study use the method of interview, observation, documentation and literature study. The Sistem development method uses a waterfall with stages of analysis, design, coding and testing. This Sistem was developed using Adobe Dreamweaver CS3, PHP, MySQL, and Xampp applications. The results of the interim research in the form of Search and Booking Hotel applications in the City of Pagar Alam web-based.